2017
DOI: 10.1016/j.breast.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Robotic nipple-sparing mastectomy for the treatment of breast cancer: Feasibility and safety study

Abstract: Background We previously devised and reported on an innovative surgical technique of robotic nipple-sparing mastectomy and immediate robotic breast reconstruction. Here we describe the outcome of the first 29 such consecutive procedures performed on breast cancer patients to assess feasibility, reproducibility and safety. Methods The following morbidity factors were tested: operation time, conversion rate to open technique, length of hospitalization, registration of complications for 1 year postoperatively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
140
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 24 publications
11
140
0
2
Order By: Relevance
“…The aim of the robotic mastectomy is to obtain the highquality aesthetic result, without any visible scars. In 2016, in "The Breast", the authors published their results and conclusions of the first phase of feasibility and safety (29).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the robotic mastectomy is to obtain the highquality aesthetic result, without any visible scars. In 2016, in "The Breast", the authors published their results and conclusions of the first phase of feasibility and safety (29).…”
Section: Methodsmentioning
confidence: 99%
“…However, they did admit that the first operation took 7 hours-this is potentially three times that of a conventional mastectomy theatre time [7]. A recent feasibility and safety study has concluded that further research into patient satisfaction and results is necessary, as it seems that robotic surgery has a very rapid learning curve and few complications, deeming it safe and potentially very effective [8].…”
Section: Current Trends and Future Researchmentioning
confidence: 99%
“…5 A low rate of conversion to open mastectomy, low rates of skin necrosis, and high degrees of patient satisfaction characterize early European experience. 6,7 The manuscript by Lai et al presents a series in which R-NSM was performed successfully in 23 breasts with immediate breast reconstruction. There was no nipple necrosis and no positive margins, and all patients were satisfied with the procedure.…”
mentioning
confidence: 99%